Osteoclast-Like Giant Cell Tumors of the Pancreas: Clinical Characteristics, Genetic Testing, and Treatment Modalities. Issue 7 (9th August 2021) - Ueberroth, Benjamin E.; Liu, Alex J.; Graham, Rondell P.; Bekaii-Saab, Tanios S.; McWilliams, Robert R.; Mahipal, Amit; Truty, Mark J.; Mody, Kabir; Sonbol, M. Bassam; Halfdanarson, Thorvardur R.
Abstract : Objectives: This study sought to better characterize patient characteristics, treatment options, and outcomes for osteoclast-like giant cell carcinoma of the pancreas, a rare subtype of pancreatic adenocarcinoma. Methods: This is a retrospective study of all patients with osteoclast-like giant cell carcinoma of pancreatic origin treated at Mayo Clinic from 2000 to present. Baseline patient characteristics, treatment modalities utilized, and outcomes were compiled. Overall survival (OS) and progression-free survival were assessed using Kaplan-Meier analysis with a significance level of P ≤ 0.05. Results: Fifteen patients met criteria for inclusion. Four patients had distant metastases at diagnosis, the remaining 11 with locoregional disease. Median OS for the entire cohort was 11 months. Metastatic disease was associated with significantly shorter OS (3.5 vs 14.1 months; P = 0.005). Three patients had no evidence of disease at time of analysis; all 3 were treated with complete resection followed by adjuvant chemotherapy. Conclusions: Osteoclast-like giant cell carcinoma of the pancreas is an aggressive malignancy with poor prognosis. For patients with locoregional disease, surgical resection followed by adjuvant chemoradiation may play a role in extended disease-free survival. Metastatic disease presents a challenging entity to treat with little data to support any effective chemotherapy regimens.